(untitled) (GEOmedia, 2018)
Most of the wheat areas in Italy are located in areas characterized by high inhomogeneities from the pedological, orographic and climatic point of view. In this context, the precision fertilization in function of crop needs, has had a positive impact on both economic and environmental sustainability. In the integrated projects of the "Pasta dei Coltivatori Toscani" chain and the " Grani Antichi Nuove Tecniche di lavorazione", supported by the Rural Development Program of the Tuscany Region, some testing farms have been provided with operating machines capable of parallel guidance and monitoring yields, precision distribution models for nitrogen fertilizer, remote monitoring systems, and a computerized business dossier capable of processing and storing parcel information. This basic knowledge informations are an important element for the improvement and extension of sitospecific field practice. In this framework, SITIfarmer software was used as a platform dedicated to precision agriculture.